Development Of Porous Medium Combustion For Micro-Power Generation Using Liquefied Petroleum Gas (LPG) Fuel - Sukardi, Mohamad Fadzli Mohd (Universiti Sains Malaysia, 2017)
In this study, the performance of porous alumina foam as a porous medium and catalytic micro combustion using Ni/Al2O3 catalyst foam using LPG as fuel were investigated. The Ni/Al2O3 catalyst foam was developed through a wet impregnation method. The performances that were being studied is the flame location produced, flue gas composition, and the efficiency of combustion process at lean combustion condition (ER of LPG/air equal to 1.9 and AFR higher than 1) and keep constant throughout the whole experiment. The combustion process started at ambient temperature produced low composition of SO2 and NOx as the total air produced of four gases (CO, CO2, SO2, and NOx) is low for all samples. The combustion efficiency increase as the decrease in porosity of alumina foam where 22 % of porosity gives the highest combustion efficiency which about 35.55 % without using nickel as catalyst compare to without using alumina foam as porous medium, 3.55 %. By the deposition of active material, Ni on the alumina foam, the same result were obtained where 22 % porosity of alumina foam gives the highest combustion efficiency which about 39.54 %, 47. 40 %, 56.73 %, and 71.39 % for the 0.1 M Ni/Al2O3, 0.25 M Ni/Al2O3, 0.5 M Ni/Al2O3, and 1.0 M Ni/Al2O3 catalyst, respectively.